Aspects of anthropotechnics reliability of materials and products for non-collapsible and collapsible systems in high-rise construction - Kazaryan Ruben (E3S Web of Conferences, 2019)
In engineering systems, which are used in construction industry and its production (buildings, constructions, roads), two fundamentally different ways of mechanical joint are used: non-collapsible and collapsible. Some architects relate non-collapsible objects to monolithic and consider their recycling as a difficult and expensive process. Compression joints on self-locking fittings can be considered as non-collapsible as well. A compression connection cannot be disassembled without destroying. Collapsible joint differs from non-collapsible by the following features: 1. You can disassemble it to original components according to a prior technology, identify and change defective elements or add some other components. 2. It requires periodic inspection and maintenance because of climatic conditions (temperature changes, pressure changes, wind loads, etc.), and the specificity of operation of this joint leads to a decrease in its mechanical properties. 3. It is forbidden to make them monolithic, so collapsible joints are mounted in an accessible way. Collapsible finishing system is a new fundamental direction of building reconstruction in the TTS system “man-technologyenvironment” in high-rise construction objects.